2003
DOI: 10.1177/154405910308200411
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteoprotegerin Gene Expression in Dental Follicle Cells

Abstract: Colony-stimulating factor-one (CSF-1) and parathyroid-hormone-related protein (PTHrP) down-regulate osteoprotegerin (OPG) gene expression in the dental follicle of the rat first mandibular molar. To examine this regulation at the signal transduction level, we treated cultured dental follicle cells with either phorbolmyristate acetate (PMA) or dibutyryl cyclic AMP (dbcAMP) to activate either protein kinase C (PKC) or protein kinase A (PKA). Our results demonstrate that PMA up-regulates OPG gene expression and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Similarly, in the present study, murine recombinant HSP25 directly enhanced the ALP activity of DFCs, in accordance with results from other studies that indicated that HSP25 could be induced in osteoblasts via protein kinase C (PKC), mitogen-activated protein kinases (MAPK), and phosphatidylinositol 3-kinase (PI3K) /protein kinase B (Akt) (Kozawa et al, 2001;Tokuda et al, 2002;Hatakeyama et al, 2002;Takai et al, 2006). Moreover, PKC gene elevation may be critical to OPG regulation in DFCs (Wise et al, 2003), and VEGF, BMP2 and BMP7 may lead DFCs to a cementoblast/osteoblast pathway through MAPK involvement (Chen et al, 2007;Kémoun et al, 2007). Thus, in the future, we will investigate further whether HSP25 regulates ALP activity through PKC, MAPK or the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, in the present study, murine recombinant HSP25 directly enhanced the ALP activity of DFCs, in accordance with results from other studies that indicated that HSP25 could be induced in osteoblasts via protein kinase C (PKC), mitogen-activated protein kinases (MAPK), and phosphatidylinositol 3-kinase (PI3K) /protein kinase B (Akt) (Kozawa et al, 2001;Tokuda et al, 2002;Hatakeyama et al, 2002;Takai et al, 2006). Moreover, PKC gene elevation may be critical to OPG regulation in DFCs (Wise et al, 2003), and VEGF, BMP2 and BMP7 may lead DFCs to a cementoblast/osteoblast pathway through MAPK involvement (Chen et al, 2007;Kémoun et al, 2007). Thus, in the future, we will investigate further whether HSP25 regulates ALP activity through PKC, MAPK or the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 78%
“…In vitro, PMA enhances the expression of PKC in the dental follicle cells, particularly PKC-a (Wise et al, 2003). In vivo, PKC-a expression is reduced at Day 3 , and this correlates with the decrease in OPG expression at Day 3.…”
Section: Discussionmentioning
confidence: 86%
“…We have hypothesized that this drop would allow osteoclastogenesis to occur for eruption (Wise et al, 2000(Wise et al, , 2002b, particularly because this is combined with the maximal expression of CSF-1 at this time . At the signal transduction level, enhancement of the gene expression and activation of protein kinase C (PKC) by PMA upregulates the expression of OPG in the dental follicle (Wise et al, 2003). In vitro, PMA enhances PKC-a and OPG expression in follicle cells, suggesting that elevation of PKC-a would enhance OPG gene expression (Wise et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations